(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
The attempt to control Onchocerciasis through the distribution of Ivermectin in Adamawa state has been ongoing for the past 20 years The current study assessed the impact of Ivermectin drugs on the prevalence of microfilaria. Eight (8) communities were selected in Four LGAs, Tongo, Song, Yola South and Hong for the study. The prevalence of microfilaria was determined using skin snip. Out of 396 Participants whose skin snip was collected only 6(2%) tested positive. The results obtained showed prevalence of microfilarial as follows; Kwapre (2%), Kukta (4%), Bolki (3%) and Ganzamanu (3%). Whereas Shashau, Dalasum, Bando and Bantaje communities had zero (0%) prevalence. Microfilaria prevalence in relation to gender was significant (P>0.05). Males had higher infection (2.0%) compared to female (1.0%). The microfilaria prevalence in these communities in 1989 was between 40-61%, compared to the current 2% in 2019 in the same selected communities. In addition, clinical signs in 1989 showed nodules 3%, Skin Disfiguration 3%, Blindness 2% while result obtained in 2019 showed Nodule 0.4%, Skin disfiguration 1% and blindness none (0.0%). In 1989 Bolki (8%) and Gangzamanu (4%) had the highest prevalence of microfilaria, but much lower in the current study 3% and 1% respectively. The results showed very low endemicity of the disease as a result of over 2 decades of Mass Drug Administration of Ivermectin in the LGAs. This implies the continuous distribution of the drugs has interrupted the transmission. Hence the objective for the administration of the drug was achieved.